Development and characterization of solid lipid nanoparticles for enhancement of oral bioavailability of Raloxifene - B Divyakant Patel; R Valay Modi; N Alok Thakkar; A Arpita Patel; P Hetal Thakkar (Wolters Kluwer Medknow Publications, 2012)
The objective of this study was to increase the oral bioavailability of Raloxifene having an absolute bioavailability only 2% due to extensive first pass hepatic metabolism by incorporating it in Solid Lipid Nanoparticles (SLNs). The optimized RSLNs prepared by Ultrasonic Emulsification and Low Temperature Solidification method showed the mean particle size, zeta potential and percentage drug entrapment of 101.4±3.5 nm, 19.4±0.279 mv, 97.67±1.02% respectively. The in-vitro intestinal permeability study indicated significantly higher permeation of the RSLNs than the marketed preparation. The in-vivo studies showed that pharmacokinetic parameters for the RSLNs were 3.5 times higher than the marketed preparation indicating significant increase in the oral bioavailability of the Raloxifene.